2022
DOI: 10.2147/amep.s355474
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Admission Tests for Medical Students’ Academic Performance

Abstract: Introduction Medical educators are concerned about predicting standardized tests for students’ academic performance in medical colleges. This study, in Saudi Arabia, attempted to analyze the predictive validity of two local standardized tests (GAT and SAAT) for students’ performance in the first two years and basic and advanced science courses. This study is unique since it focuses on comparing the prediction of both tests between the two years and examining the difference in students’ performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The study found a significant positive association between pre-admission student scores and their academic performance [ 9 ]. Similar studies found that GAT and SAAT have the strongest relationship to student performance in medical college in Saudi Arabia [ 10 ]. Other studies of Clinical Biochemistry students at King Adulaziz University showed a weak correlation between SAAT and student performance [ 11 ].…”
Section: Introductionmentioning
confidence: 61%
“…The study found a significant positive association between pre-admission student scores and their academic performance [ 9 ]. Similar studies found that GAT and SAAT have the strongest relationship to student performance in medical college in Saudi Arabia [ 10 ]. Other studies of Clinical Biochemistry students at King Adulaziz University showed a weak correlation between SAAT and student performance [ 11 ].…”
Section: Introductionmentioning
confidence: 61%
“…Prior studies have also demonstrated an association between academic performance and admission test scores. These studies concluded that admission test scores can be reliable predictors of academic success and the likelihood of graduation [ 3 , 6 , 20 , 21 ]. However, it is important to take into consideration that test performance can be affected by a magnitude of factors.…”
Section: Discussionmentioning
confidence: 99%